DETERMINAN PENURUNAN RETURN ON EQUITY (ROE) SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Rois, Muhammad; Wijayanto, Edi; Berliana, Dinar (KEUNIS, 2021)
This study reveals a decreased ROE performance, and this contradicts the Return On Equity (ROE) theory which states that a good ROE is an increase over time. This study aims to analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), Inventory Turnover (ITO), and Sales Growth (SG) towards ROE. The study design was quantitative research applied causal. The research sample used the purposive sampling method, the sample in this study were 9 Manufacturer Companies listed on the Indonesia Stock Exchange in 5 years. The analysis in this study is a panel linear multiple regression analysis models using Eviews 9.0. The analysis results in an Adjusted R2 value of 0,488777, indicating that changes in the independent variables can contribute 48,8777% to changes in the dependent variable. In comparison, 51,1223% are influenced by another factor not included in the model. The t-test results show that the variable CR and ITO have a significant effect on ROE, while the DER and SG have no significant effect on ROE.